2012
DOI: 10.5301/ejo.5000194
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy for Vitreoretinal Complications of Behçet Uveitis

Abstract: Purpose. To evaluate the role of pars plana vitrectomy (PPV) for the treatment of vitreoretinal complications of ocular Behçet disease (BD).
Methods. Retrospective review of the medical records of all patients who underwent PPV for vitreoretinal complications of Behçet uveitis in the Ophthalmology Department of the Hospital Clinic of Barcelona, Barcelona, Spain, from January 1994 until December 2011. Preoperative and postoperative best-corrected visual acuities (BCVA), ocular findings, treatments, surgical ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The results in the current study are still comparable with the data published by Heiligenhaus et al [21], who recommended a preoperative control of intraocular inflammation prior to the vitrectomy procedure to decrease the risk of complications, and Mesquida et al, with reported favorable results following pars plana vitrectomy in the Bechet eyes with no reported postoperative complications and recorded control of ocular inflammatory condition and the reduce in postvitrectomy systemic treatment [22]. …”
Section: Discussionsupporting
confidence: 88%
“…The results in the current study are still comparable with the data published by Heiligenhaus et al [21], who recommended a preoperative control of intraocular inflammation prior to the vitrectomy procedure to decrease the risk of complications, and Mesquida et al, with reported favorable results following pars plana vitrectomy in the Bechet eyes with no reported postoperative complications and recorded control of ocular inflammatory condition and the reduce in postvitrectomy systemic treatment [22]. …”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, nongranulomatous uveitis, such as Behçet's disease [29,30,31], occurs recurrently and presents an acute type of inflammation [32], and surgical outcomes have sometimes been poor [33,34,35]. …”
Section: Introductionmentioning
confidence: 99%